Making Sense of a Multi-Protagonist Film: Audience Response Research and Robert Altman’s Short Cuts (1993) - Azcona, M. Mar (Miscelánea: A Journal of English and American Studies, 2005)
This article explores the ways in which some of the unconventional narrative strategies used in multi-protagonist movies, namely, the multiplicity of characters, the abandonment of conventional notions of causality and the restriction of spectator involvement in the film may affect spectators’ comprehension of the narrative. My evidence comes from an audience research investigation on Robert Altman’s Short Cuts (1993). It attempts to show both the potentials and limitations of audience response study, which should not be seen as a substitute but rather as a supplement to scholarly theorization and analysis.